Performance of HKUST-1 Metal-Organic Framework for a VOCs mixture adsorption at realistic concentrations ranging from 0.5 to 2.5 ppmv under different humidity conditions. Issue 3 (June 2019) - Chevalier, V.; Martin, J.; Peralta, D.; Roussey, A.; Tardif, F.
Highlights: Adsorption capacity of HKUST-1 framework at very low concentrations for toluene, acetone, o-xylene, ethanol & acetaldehyde (respectively 23.8, 5.0, 14.7, 16.5 and 1.4%wt). VOCs are adsorbed in the order of: o-Xylene > Acetone > Toluene. Adsorption capacities are reduced notably, up to 97% loss with humidity increase. Cold desorption tests show a 50% decrease of the adsorption capacity after three cycles. Abstract: In this study, HKUST-1 framework utilization as an adsorbent was characterized in realistic indoor air conditions. Adsorption capacities and breakthrough behaviors of this material were studied for low concentration gas mixtures with controlled relative humidity. Results demonstrate high adsorption capacities (23.8, 14.7, 16.5, 5.0, and 1.4%wt for the respective mono-pollutant gases: toluene, o-xylene, ethanol, acetone and acetaldehyde). The adsorption capacities and breakthrough curves of binary and five gases mixtures give information about the competitions between pollutants and show that the studied volatile organic compounds (VOCs) are adsorbed in the order of: o-Xylene > Acetone > Toluene. Cold desorption tests were also conducted and showed a 50% decrease of the adsorption capacity after three cycles.